#TITLE_ALTERNATIVE# - HIMAWAN, RAKHMAT
Hard chromium platings are generally used in engineering applications that require a high surface hardness especially for wear resistance. To obtain a high quality coating, the process should be optimized by having a close control on the plating parameters. In this research the use of lead oxide other than ordinary lead anode were both observed, especially their effect on the hardness and current efficiency. Besides, it was also observed the influence of CrO3 concentration variations in electrolyte and plating time. CrO3 concentrations were varied between 125 to 275 g/l and plating time between 40 to 80 minutes, these were to achieve an uniformly high hardness. Coating with current density of 80 A/dm2 and temperature of 55 oC showed a relatively more uniform hardness of 874 ± 22 VHN, with 250 g/l CrO3 and 70 minutes plating time. The attempt to use a lead dioxide anode (PbO2) was carried out in order to prevent the formation of lead chromate layer (PbCrO4) in lead anode that would decrease current efficiency. In fact at a current density of 80 A/dm2, temperature of 55 oC, CrO3 concentration of 250 g/l, and 40 minutes plating time, it appeared that the current efficiency in suppossed “lead dioxide” anode was lower than ordinary lead anode (? “lead dioxide” = 8.5 %, ? lead = 10.5 %). This may be caused by the formation of lead suboxide layer (Pb2O) instead of lead dioxide on the anode surface. Further investigation should be carried out to convince that the lead dioxide anode is truely developed and there is no change of oxide layer on plating bath. The influence of lead dioxide anode to current efficiency also need to be studied further.